AMERICAN GERIATRICS SOCIETY MEMBER SURVEY ON THE "UNBEFRIENDED". (11th November 2018) - Catlin, C; Farrell, T W; Naik, A; Widera, E; Moye, J
Abstract: In 2016, the American Geriatrics Society (AGS) released a position statement with guidance for clinical practice and public policy to better serve the "unbefriended" (adults lacking decision-making capacity, advance directives, and surrogates). To learn more about medical providers' experiences and innovative practices in working with this vulnerable population, 120 AGS members were surveyed. Participants worked in inpatient (36.9%) and outpatient (63.1%) settings across the U.S. They reported that "unbefriended" patients face problems such as medically unnecessary hospital stays, delays in treatment and care transitions, and loss of rehabilitation potential. Consultation with teams and ethics committees and securing a guardianship were seen as helpful, though some physicians reported making decisions on their own without a legal surrogate. Participants offered suggestions on how to prevent adults from becoming "unbefriended." Participants also shared preferences for possible alternatives to the term "unbefriended, " which many find stigmatizing.